Pengaruh Penggunaan Media Mistery Box terhadap Kemampuan Menulis Karangan Narasi pada Pelajaran Bahasa Indonesia Siswa Kelas V SD di Kabupaten Gow - Fitri Ramadhani; Sulfasyah Sulfasyah; Syekh Adiwijaya Latief (Departement of Mathematics Education, 2024)
This research aims to find out if there is an influence of the Mystery Box media on the ability to write narrative essays in Indonesian language lessons for fifth grade students at SD Inpres Tamattia, Gowa Regency. The type of research used is pre-experimental one-group pretest-posttest design. With a total of 20 students. The research instrument was a narrative essay writing test. Data analysis uses descriptive analysis and inferential analysis. The results of the research show that there is an influence of using mystery box media on the ability to write narrative essays in Indonesian language lessons for fifth grade students at SD Inpres Tamattia. This can be seen in the increase in grades obtained by students. The average value of the pretest results before applying the mystery box media was 47.40. After implementing the mystery box media, the posttest score reached 89.30. Furthermore, the results of inferential analysis using the t-test show that the tcount value > tTable value or 13.976 > 2.093 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that the mystery box media influences the ability to write narrative essays in Indonesian language lessons for fifth grade students at SD Inpres Tamattia.